Sward structure and livestock performance in guinea grass cv: Tanzania pastures managed by rotational stocking strategies (Scientia Agricola, 2014)
Grazing strategy is a key element in the determination of sward structure, herbage nutritive value and animal performance. We aimed to compare the herbage characteristics and performance of livestock in pastures of Panicum maximum cv. Tanzania managed, using two rotational stocking strategies, which provided either a fixed-length rest period (FRP) of 35 days in the spring and fall and 30 days in the summer, or a variable-length rest period (VRP), determined by the time required for the canopy to achieve 70 cm in height. The pastures were evaluated in the pregrazing condition for forage mass (FM); leaf (LP), stem (SP) and dead matter (DP) percentages; and nutritive value (NV). The animals were weighed every 28 days. Pastures managed with the FRPs exhibited greater FMs, SPs and DPs and lower LPs and NVs than those managed with the VRPs. The average daily livestock weight gain was greater during the spring and summer for the VRP than for the FRP pastures, resulting in an average animal weight gain per area of 990 and 860 kg ha−¹ wet period−¹ for the pastures managed with the VRPs and FRPs, respectively. Thus, pasture rest periods that were maintained after the sward reached 70 cm in height reduced the animal performance on Tanzania guinea grass.